Progressive osseous heteroplasia: A rare case report - Kananbala Sahu; Arpita N Rout; Liza Mohapatra; Prasenjeet Mohanty (Indian Dermatology Online Journal, 2020)
Progressive osseous heteroplasia (POH) is a rare genetic condition of progressive extraskeletal bone formation. POH is clinically suspected by cutaneous ossification, usually presenting in early life, that involves subcutaneous and then subsequently deep connective tissues, including muscle and fascia. We report a case of POH in a 3-year-old child with multiple nontender subcutaneous nodules which, on radiology and histopathology, showed intracutaneous bone formation. Although there is no specific and effective treatment, knowledge about this entity is necessary for early detection and genetic counseling of parents.